Predictive value of the tuberculin skin test and QuantiFERON-tuberculosis Gold In-Tube test for development of active tuberculosis in hemodialysis patients - Seyhan, Ekrem Cengiz; Günlüoğlu, Gülşah; Günlüoğlu, Mehmet Zeki; Tural, Seda; Sökücü, Sinem (Medknow Publications, 2016)
Background: Hemodialysis (HD) patients are at increased risk of reactivation of latent tuberculosis infection (LTBI) compared with the general population. QuantiFERON-TB Gold (QFT-G) for LTBI detection is more promising than tuberculin skin test (TST) in HD patients. AIM: In our study, we evaluated the value of the TST and QFT-G In-Tube (QFG-IT) test in the development of active tuberculosis (TB), in the HD patients, and in healthy controls. Methods: The study enrolled 95 HD patients and ninety age-matched, healthy controls. The TST and QFG-IT were performed. All the subjects were followed up 5 years for active TB disease. Results: Compared to the healthy controls, a high prevalence of LTBI was found in the HD patients by QFG-IT (41% vs. 25%). However, no significant difference was detected by TST (32% vs. 31%). Four HD patients and one healthy control progressed to active TB disease within the 5-year follow-up. For active TB discovered subjects, QFG-IT was positive in all, but TST was positive in two (one patient and one healthy control). In HD patients; sensitivity, specificity, positive and negative predictive values of QFG-IT, and TST for active TB was 100% and 25%, 62% and 67%, 10%, and 3%, and 100% and 95%, respectively. Receiver operating curve analysis revealed that the results are significantly different (P = 0.04). Conclusion: QFG-IT test is a more useful diagnostic method than TST for detecting those who will progress to active TB in HD patients.
Keywords: Active Tuberculosis; Healthy Controls; Hemodialysis Patients; QuantiFERON-Tuberculosis Gold In-Tube; Tuberculin Skin Test